Exceeding Workplace-related Issues: Psychological Contract Breach and Its Effects as Experienced by Indonesian Academics - Firmansah, Yayan; Abdul Hamid, Zabeda; Mhd Sarif, Suhaimi (Sharia Business Management UIN Raden Intan Lampung, 2023)
The main objective of this research is to examine how Indonesian academics experienced breaches in their psychological contract, and how the breaches affected them. Previous studies on academics psychological contract breaches have mainly focused on how the stressful event is experienced and have mostly ignored the effects of the breaches. Through a phenomenological approach, this study interviewed eleven Indonesian academics, leading to two main discoveries. The first finding concerns the types of PCB experienced by these academics, which encompassed transactional and relational breaches. The second discovery is about the impacts of such breaches, which included negative emotional experiences and their daily work activities. Furthermore, these stressful events not only impacted their emotions and work but also their social lives.